Collaborative Quest for Quality - Washington, Valerie M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
A collaborative effort between an elementary school (P.S.86) and Lehman College, both located in New York City, is described in this paper. The project was designed with the objective of avoiding the usual "top-down" process and instead concentrating on cooperative and collaborative planning. The participants included one college faculty member, a research assistant, three volunteer fifth-grade teachers, and their classes. The focus of the program was integration of writing, reading, and study skills emphasizing the development of research skills. The physical environment and a lack of financial resources presented obstacles to implementation. Also, teachers had to be willing to try an interdisciplinary approach to the curriculum. The students' lack of experience at independent research became a difficulty that had to be overcome. Individual self-instructional learning modules were developed. A core group of children was trained to be peer teachers. The outcomes reported include positive growth in collegiality among the teachers, development of a sense of community by the children, and an expansion of the concept of collaboration by the Lehman participants. References are appended. (LMS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College School Cooperation; Collegiality; Cooperative Planning; Cooperative Programs; Elementary Education; Higher Education; Integrated Curriculum; Research Skills; New York; Reports, Descriptive